2013
DOI: 10.1002/jbmr.2111
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Dose Requirement to Raise 25-Hydroxyvitamin D to Desirable Levels in Adolescents: Results from a Randomized Controlled Trial

Abstract: Several organizations issued recommendations on desirable serum 25-hydroxy vitamin D [25(OH)D] levels and doses of vitamin D needed to achieve them. Trials allowing the formulation of evidence-based recommendations in adolescents are scarce. We investigated the ability of two doses of vitamin D 3 in achieving recommended vitamin D levels in this age group. Post hoc analyses on data from a 1-year double-blind trial that randomized 336 Lebanese adolescents, aged 13 AE 2 years, to placebo, vitamin D 3 at 200 IU/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 47 publications
(58 reference statements)
8
20
1
2
Order By: Relevance
“…A deficiency in vitamin D has indeed been observed in different studies and categories of the Lebanese population (adolescents, university students, adults, and postmenopausal women) (Gannagé-Yared et al, 2003;Gannagé-Yared et al, 2009a, b, 2010Al-Shaar et al, 2014;Hoteit et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…A deficiency in vitamin D has indeed been observed in different studies and categories of the Lebanese population (adolescents, university students, adults, and postmenopausal women) (Gannagé-Yared et al, 2003;Gannagé-Yared et al, 2009a, b, 2010Al-Shaar et al, 2014;Hoteit et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Figure 1, which shows the data from the twenty most reliable and homogeneous studies [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], exhibits a positive correlation between amounts of oral vitamin D administered and change in serum vitamin D levels. Figure 1 shows the change in vitamin D serum levels from the most rigorous studies that gave daily doses of cholecalciferol.…”
Section: Resultsmentioning
confidence: 83%
“…We found 25 informative studies which showed a significant dose-response between oral supplementation and serum levels of vitamin D with an r 2 of 0.61.These data are consistent with single studies and meta-analyses.In conclusion, the data show a consistent relationship that appears to be independent of multiple confounders. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Nine studies meeting our criteria evaluated individuals with disease included individuals with vitamin D deficiency [23,24], individuals with diabetes [25][26][27], relapsing multiple sclerosis patients [28], individuals with early stage prostate cancer [29], patients with previous hip fractures [30], and Parkinson Disease [31].…”
Section: Introductionmentioning
confidence: 98%
“…They found many factors to be associated with reaching the desired level, such as baseline 25-(OH)D concentration, supplementation dose, and factors influencing vitamin D metabolism. 30,31 According to the Dutch guidelines, supplementation is recommended without measuring the vitamin D level. 7,25 Based on multivariate analysis in our study, the only factor significantly associated with 25(OH)D concentration at 15 months was baseline 25-(OH)D concentration.…”
Section: Figurementioning
confidence: 99%
“…It seems that the effect in these children differs from that in healthy children. [26][27][28][29][30][31] We investigated the factors that are associated with serum 25-hydroxyvitamin D (25-(OH) D) concentrations in children with epilepsy and intellectual disability. We will also determine whether supplementation in doses which were at least equal to the amount recommended by the guidelines leads to a sufficient vitamin D status in all these children after 6 and 15 months.…”
Section: Introductionmentioning
confidence: 99%